Open Distance Learning as a Catalyst for Enhancing Digital Literacy and Green Technology in Technical and Vocational Education and Training (TVET) in South Africa - Lehloka, Motlatsi Cletus (Journal of Ecohumanism, 2025)
The aim of this paper is to investigate how Open Distance Learning (ODL) might improve digital literacy and support green technologies within the Technical and Vocational Education and Training (TVET) sector in South Africa. Case studies and interviews with teachers, students, and industry partners engaged in TVET programs were used in a qualitative approach. Thematic study of the data clarified how ODL affects digital literacy and the acceptance of green technologies. The results show that ODL greatly increases student access to instructional resources, hence promoting digital literacy. It helps to include green technologies within the course so that students have the necessary understanding for sustainable living. The study stresses the need of tools and ongoing assistance in order to enjoy these benefits. This paper shows how ODL may be a transforming instrument in the South African TVET sector. It underlines the need of digital competences and sustainability in vocational education, thereby providing fascinating data for legislators and educational institutions trying to increase the relevance and efficiency of TVET programs in a fast-changing technology environment.